JUMPA Vol.4 No.2, Juni 2017 PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN CITRA MEREK TERHADAP LOYALITAS KONSUMEN MELALUI KEPUASAN KONSUMEN HYPERMARKET GIANT TANGERANG DAN TANGERANG SELATAN: PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN CITRA MEREK TERHADAP LOYALITAS KONSUMEN MELALUI KEPUASAN KONSUMEN HYPERMARKET GIANT TANGERANG DAN TANGERANG SELATAN - Rahayu Lestari Universitas Nasional; Elwisam Universitas Nasional (Jurnal Manajemen dan Perbankan (JUMPA), 2017)
Respondents in this study is that consumers who buy and use as well as to comment that shopping at Giant Hypermarket has advantages and higher profits so that consumers feel the satisfaction of making loyal than the other hypermarkets. Although many consumers find the allure of the many product options, the reality is sometimes confused by the participating consumer kadng the product selection. The urge to constantly consume a product must also be influenced by various factors such as taste, price, product quality, and no less important is the brand of the product itself which can sometimes be the main determinant. Based on the phenomenon that exists in the environment community Tangerang and South Tangerang, the authors conducted research to analyze the influence Effect of Product Quality, Price Strategy and Brand Loyalty Through Consumer Satisfaction Consumer Giant Hypermarket Tangerang and South Tangerang. The analysis technique used to answer this hypothesis using Structural Equation Model (Structural Equation Modeling or SEM) is processed with the help of software Amos 21.0. The samples used as many as 200 people as consumers Giant Hypermarket. The analysis showed that the brand image affects customer satisfaction, while the quality of the products and pricing Persepsies have no effect on customer satisfaction. While customer satisfaction effect on consumer loyalty.